Analisis Pengelolaan Dana Desa dalam Upaya Pembangunan Desa untuk Meningkatkan Kesejahteraan Petani Desa Purwodadi Kecamatan Sunggal (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine the factors of potential, human resources, capital, village fund allocation, consumption, infrastructure and family responsibilities relevant to improving the welfare of farmers in Purwodadi Village, Sunggal District. The implementation of regional autonomy and decentralization aims to improve the efficiency and effectiveness of resource management, the quality of public services, and community welfare. Empowerment based on village development through village funds focuses on improving welfare, the quality of human resources, and reducing poverty by utilizing local potential, so that the village becomes independent. Although Purwodadi Village has a significant budget and economic potential, the welfare of its people is still low. This is reflected in the income that depends on the traditional and simple agricultural sector, and the condition of the houses which are still very simple. In addition, the management of village funds is less transparent and professional, with the distribution of aid that is not evenly distributed, causing public distrust of the management of these funds and contributing to the low level of welfare. This study uses the Confirmatory factor analysis (CFA) and Multiple Linear Regression statistical analysis models, with a total of 150 respondents collected by distributing questionnaires. The results of the Confirmatory Factor Analysis (CFA) analysis show that of the seven factors, four factors that are worthy of increasing the welfare of farmers in Purwodadi Village, Sunggal District have a significant influence, including potential, capital, infrastructure and village fund allocation. The results of multiple linear regression show that in the partial hypothesis test, these four factors have a significant influence on increasing the welfare of farmers in Purwodadi Village, Sunggal District and in the simultaneous hypothesis, potential, capital, infrastructure and village fund allocation together have a positive and significant influence on the welfare of farmers in Purwodadi Village, Sunggal District.